Investigation and genetic confirmation of the Cryptosporidium species in fish handlers in Baghdad city. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The present study aims to investigate molecular confirmation for Cryptosporidium species in fish handlers in Baghdad City, central Iraq. Materials and Methods: Sixty stool samples were collected between early November 2023 and late April 2024. All samples were examined phenotypically using a modified Ziehl-Neelsen stain and genotypically (nested polymerase chain reaction technique) based on a partial sequence of 18S rRNA genes with sequencing and phylogenetic tree analysis. Results: The total molecular results identified Cryptosporidium parvum with an infection rate of 45% (27/60). A higher infection rate of 51.9% (14/27) was found in the age group between 15 and 35 years, and male handlers recorded a lower infection rate (45%) than females (41.6%). April had a higher elevation in the infection rate of 60% (6/10) than other months. Conclusion: The C. parvum was the only species found in fish handlers, and these local isolates have higher similarity with other isolates of China and Iran.J. Adv. Vet. Anim. Res., 12(1): 1–7, March 2025http://doi.org/10.5455/javar.2025.l866